2021
DOI: 10.1021/acs.nanolett.0c03740
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Wave Emission from Vortex Cores under Static Magnetic Bias Fields

Abstract: We studied the influence of a static in-plane magnetic field on the alternating-field-driven emission of nanoscale spin waves from magnetic vortex cores. Time-resolved scanning transmission X-ray microscopy was used to image spin waves in disk structures of synthetic ferrimagnets and single ferromagnetic layers. For both systems, it was found that an increasing magnetic bias field continuously displaces the wave-emitting vortex core from the center of the disk toward its edge without noticeably altering the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…More recently, S. Mayr et al experimentally demonstrated, by using of TR-STXM measurements, that the SW emission pattern of a magnetic vortex core can be manipulated by the application of an in-plane static magnetic field [63]. In particular, they studied SW generation from magnetic vortex cores stabilized in disk structures having a diameter of 3 µm and patterned by electron beam lithography in both a SFi system consisting of a Co(48nm)/Ru(0.8nm)/Ni81Fe19(45nm) trilayer and a single Py film 100 nm thick.…”
Section: Tunable Spin-wave Emission From Vortex Coresmentioning
confidence: 99%
“…More recently, S. Mayr et al experimentally demonstrated, by using of TR-STXM measurements, that the SW emission pattern of a magnetic vortex core can be manipulated by the application of an in-plane static magnetic field [63]. In particular, they studied SW generation from magnetic vortex cores stabilized in disk structures having a diameter of 3 µm and patterned by electron beam lithography in both a SFi system consisting of a Co(48nm)/Ru(0.8nm)/Ni81Fe19(45nm) trilayer and a single Py film 100 nm thick.…”
Section: Tunable Spin-wave Emission From Vortex Coresmentioning
confidence: 99%
“…The vortex cores located on the top and bottom surfaces of the disk are no longer coaxial and the two vortex cores on the top and bottom surfaces of the disk are connected through the domain wall stretched along the x-axis (See Supplementary Fig. 1 and Supplementary Note 1), which indicates that the VC 3 structure is clearly a 2D vortex core structure (See orange dotted arrows) 21,40,[46][47][48][49][50][51] . We confirmed that the dimensional change of the vortex core structure starts occurring at H x = 15 mT, and the domain wall connecting the vortex cores on the top and bottom surfaces of the disk gets longer as H x increases until the vortex core structure is annihilated at H x = 62 mT (See Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, we proposed a design of spintronic oscillators based on DMI, which has shown great potential in the applications of neuromorphic computing and tunable spin wave emitters 52,53 . Through a systematic study, we revealed the basic dynamic properties of the oscillator and achieved precise manipulation of the oscillator with spin polarized current and magnetic field.…”
Section: Main Textmentioning
confidence: 99%